Digital Transformation and AI Literacy for Strengthening MSME Innovation and Sustainability - Retno Purwani Setyaningrum; Sari Laelatul Qodriah; Surya Bintarti; Tri Ngudi Wiyatno; Eki Prafitri Rahmadani (Lentera Ilmu Nusantara, 2026)
Digital transformation and the advancement of Artificial Intelligence (AI) technologies have become essential factors in enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs in Bekasi Regency continue to face challenges, including low levels of digitalization, limited utilization of AI, inadequate technology-based innovation capacity, and insufficient implementation of sustainable business practices. This community service program aimed to strengthen the capacity of MSMEs through a digital transformation and AI-based mentoring initiative. The implementation method consisted of several stages, including socialization, training, technology adoption, mentoring, evaluation, and sustainability reinforcement. The results demonstrated significant improvements in participants’ abilities to utilize digital applications for financial recording, inventory management, and business monitoring. In addition, participants showed increased literacy and practical skills in applying AI for digital marketing, market analysis, and business strategy development. The program also encouraged data-driven product and marketing innovation while raising awareness of efficient and sustainable business practices. Overall, the mentoring activities successfully enhanced the capacity of MSMEs to address digital transformation challenges and established a foundation for more innovative, competitive, and sustainable business development.